(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Clinical trials can be conducted on the basis of one research center in one country, or they can be multicenter and take place simultaneously in many countries.